The impact of age on changes in quality of life among breast cancer survivors treated with breast-conserving surgery and radiotherapy - Bantema-Joppe, E J; de Bock, G H; Woltman-van Iersel, M; Busz, D M; Ranchor, A V; Langendijk, J A; Maduro, J H; van den Heuvel, E R (British journal of cancer, 2015)
Background: The purpose of the study was to determine the impact of young age on health-related quality of life (HRQoL) by comparing HRQoL of younger and older breast cancer patients, corrected for confounding, and of young patients and a general Dutch population. Methods: The population consisted of breast cancer survivors (stage 0-III) after breast-conserving surgery and radiotherapy. Health-related quality of life was prospectively assessed using the EORTC QLQ-C30 and QLQ-BR23 questionnaires. The association between age (⩽50; 51–70; ⩾70 years) and HRQoL over time was analysed with mixed modelling. The clinical relevance of differences between/within age groups was estimated with Cohen’s D and consensus-based guidelines. The HRQoL data from the young patient cohort were compared with Dutch reference data at 3 years after radiotherapy. Results: A total of 1420 patients completed 3200 questionnaires. Median follow-up was 34 (range 6–70) months. Median age was 59 (range 28–85) years. Compared with older subjects, young women reported worse HRQoL in the first year after radiotherapy, but clinical relevance was limited. Three years after radiotherapy, HRQoL values in the younger group were equal to those in the reference population. Pain and fatigue after radiotherapy improved, with medium clinical relevance. Conclusions: Three years after radiotherapy for breast cancer, young age was not a risk factor for decreased HRQoL.